ANALYSIS OF THE SOCIAL STATUS DIFFERENCES AMONG THE QIDAN BASED ON DENTAL HEALTH - Linhu ZHANG; Dong WEI (Mongolian Journal of Anthropology, Archaeology and Ethnology, 2008)
The Qidan were considered a powerful nomadic confederacy of the eastern Xianbei. In 344 A.D., the Qidan were separated from Xianbei and disappeared as an independent people since they were overwhelmed by the Nuzhen in 1124A.D. Tooth wear was observed and compared on the remains from several archeological sites in western Liaoning, east and central southern Inner Mongolia. Based on artifact assemblages and tomb writings, three sites were determined to be the burials of Qidan nobility, and three sites were determined to be the cemeteries of commoners. The process of tooth-wear is continual from tooth eruption to death. Age is one of the most important factors affecting tooth-wear. In addition, the diet, food preparation, occlusive relations, and health conditions of the teeth affect the tooth-wear of archaeological populations. Comparing the tooth-wear between the elite and commoners of Qidan of the same age, we see that the average tooth-wear rate is lower in the elites than in the commoners. The dental diseases in the elite are also less common than those detected in Qidan commoners. Based on the analyses we conclude that the customs of using teeth and the food ingredient in the diet are different between the commoners and elite.